Improving Road Infrastructure with the Support of European Funds. EUSDR - A Strategic Tool Used to Fund Projects in Galati County: Array - Panaitescu, Manuela (Journal of Danubian Studies and Research, 2020)
The study analyzes the strategy used in Galati County for the improvement of the road infrastructure with the support of European funds. The European Union Strategy for the Danube Region (EUSDR) can finance various areas - infrastructure development, human resource development, environmental protection, etc. The road infrastructure rehabilitation and modernization projects amount to over 300 km of the county road. There are works to consolidate the road, rehabilitate all bridges and footbridge, arrange pedestrian spaces, widen the road, where necessary, and, of course, asphalting.